Analisa Dampak Faktor Organisasi Dan Perseorangan Terhadap Hasil Yang Berorientasi Mutu - Dompas, Saartje Laoh (JBE (Journal of Business and Economics); Volume 8 No.1, 2009 JBE UNKLAB, 2009)
Quality-oriented goals and values have an impact on the demand of the organization (e.e., continuous improvement of processes, learning; a customer focus), and affect the design of internal systems. Furthermore, the success of a total quality management (TQM) program depends on the degree to which the internal systems (e.g., design of jobs, human resources policies) are consistent with the goals and values of the organization. Characteristics and abilities of individuals may affect individual and quality-related outcomes. Moreover, the success of a TQM program may be highly dependent on the congruence between and individual's values, abilities, needs, and the requirements of the system. Individuals can either be matched to the system or the organizational system can be modified to meet the values, abilities and needs of individuals. And quality-related outcomes are jointly determined by organizational and individuals factors